2009
DOI: 10.1186/1479-5868-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured physical activity of USA adults by sex, age, and racial/ethnic groups: a cross-sectional study

Abstract: Background: Accelerometers were incorporated in the 2003-2004 National Health and Nutritional Examination Survey (NHANES) study cycle for objective assessment of physical activity. This is the first time that objective physical activity data are available on a nationally representative sample of U.S. residents. The use of accelerometers allows researchers to measure total physical activity, including light intensity and unstructured activities, which may be a better predictor of health outcomes than structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
101
4
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 22 publications
(17 reference statements)
18
101
4
4
Order By: Relevance
“…One study in Iran showed that age was related with physical activity and the level of physical activity decreased with increasing age (Momenan et al, 2011). Similar findings have also been reported in other studies (Abdi, 2015;Bergman, 2008;Hawkins et al, 2009). It appears that with increasing age and the incidence of motor disorders and non-communicable diseases, the level of RPA decreases and health planner and authorities need to pay close attention to this important issue.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…One study in Iran showed that age was related with physical activity and the level of physical activity decreased with increasing age (Momenan et al, 2011). Similar findings have also been reported in other studies (Abdi, 2015;Bergman, 2008;Hawkins et al, 2009). It appears that with increasing age and the incidence of motor disorders and non-communicable diseases, the level of RPA decreases and health planner and authorities need to pay close attention to this important issue.…”
Section: Discussionsupporting
confidence: 81%
“…The findings of the previous studies show that there is a strong relationship between physical activity with age, gender, employment status, education level and marital status (Abdi, 2015;Hazavehie et al, 2013). According to the findings, lack of physical activity is more common in women than in men and in older age groups (Hallal, 2012;Hawkins et al, 2009). It appears that physical activity in middle age, especially in middle-aged women, leads to lifestyle modifications that extend in to older ages and enhances their quality of life (Barg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, physical activity tends to decrease with age. Hawkins found this to be true for all ethnicities and races in the USA [31]. A study of 19,145 Malaysians produced similar results.…”
Section: Discussionsupporting
confidence: 64%
“…Estos resultados se asemejan a los ya encontrados por otros autores (Hawkins et al, 2009;Trinh et al, 2008) y siguen la misma tendencia encontrada en poblaciones de otras latitudes, como sucede en el caso de la poblaciĂłn Australiana, donde las mujeres presentan mayores niveles de inactividad fĂ­sica, (Victorian Health Promotion Foundation; 2011). Tales diferencias encontradas entre gĂ©neros pueden ser atribuibles a diversos factores, desde la estigmatizaciĂłn social hacia el ejercicio fĂ­sico y deporte (Loland, 2000;Moreno et al, 2006), que trae consigo el abandono de dichas prĂĄcticas por parte de las mujeres a tempranas edades y que repercute en edades posteriores.…”
Section: Discussionunclassified